Pengaruh Konsumsi Tablet Tambah Darah terhadap Kadar Hemoglobin (Hb) saat Menstruasi pada Remaja Putri di SMK Maesan - Ikromatul Hasanah; Riska Faraswati; Suhartin (PT. PENERBIT TIGA MUTIARA, 2026)
Menstruation is a physiological process that can cause regular iron loss in adolescent girls, thereby potentially reducing hemoglobin levels and increasing the risk of anemia if not balanced with adequate iron intake. The research problem focuses on whether the consumption of iron supplementation tablets affects hemoglobin levels during menstruation among adolescent girls at SMK Maesan. This study aims to analyze the effect of iron supplementation on changes in hemoglobin levels using a quasi-experimental design with a control group pretest-posttest approach. The sample consisted of 30 respondents selected through purposive sampling based on inclusion criteria. Hemoglobin levels were measured using the cyanmethemoglobin or Sahli method, accompanied by standard procedures for administering iron supplements. The results of the Wilcoxon statistical test showed a p-value of 0.000 with α<0.05, indicating that the null hypothesis was rejected and the alternative hypothesis was accepted, meaning that there was a significant effect of iron supplementation on increasing hemoglobin levels during menstruation. These findings confirm that the intervention of iron supplementation is effective in improving hemoglobin levels in menstruating adolescent girls. The novelty of this study lies in emphasizing the effectiveness of controlled iron supplementation interventions among vocational high school adolescents using a pretest-posttest approach, thereby providing practical contributions to anemia prevention efforts from an early age through structured and sustainable school health programs.